Motion Analysis of the Inner Pipeline Inspection Cleaning Robot - Chang Qi; Yan Hongwei; Niu Hailong; Zhao Pengyang; He Bolong (Jixie chuandong)
Aiming at the low efficiency and poor accuracy of manual inspection in pipeline cleaning operation, and the problems of pipeline maintenance, a spiral drive pipeline inspection and cleaning robot was proposed, which is driven by the spiral drive to ensure stable operation in the pipeline, adapts to the change of pipeline diameter through the adaptable way of spring reducers, and cleans the dirt in the pipeline by the combination of mechanical cleaning and high pressure water jet cleaning. Through the force analysis of the driving wheel body of the robot, the tractive force analysis model and the straight tube motion model of the robot driving unit were established. At the same time, the motion process of the robot in the tube was analyzed by using the coordinate transformation method, and the motion characteristics of the robot were studied. Finally, the traction force and velocity of the robot in the straight pipe were simulated and verified by experiments. The results show that the actual speed of the robot is 0.075 m/s, and the minimum tractive force in compliance with the design index is 39 N. It is concluded that the speed of the robot in the process of passing the straight pipe is positively correlated with the tangent value of the deflection angle of the driving wheel, and the simulation analysis results are basically consistent with the actual situation. The research of the inspection and cleaning robot has certain reference value for the cleaning and maintenance of pipelines.